A perspectiva dos gestores sobre a participação do usuário no projeto e a redução do tempo de processo - Ebisui, Victor Centurion (Universidade Federal de São Carlos, 2021)
Historically the market has become more dynamic and competitive, so customers needs and desires have become increasingly refined. Thus, clearly understanding the requirements and making the product available at the right time to the market become crucial competitive force for the business. As a result, the present study aimed to carry out an analysis seeking to identify an existing relationship between the use of customer interaction in the development phase of a new product, reducing the time of the project execution and, consequentialy, the time-to-market. This work was developed from a quantitative analysis in a consumer goods company from school supplies sector. For the evaluation of the central question, a questionnaire was made for people responsible to lead the new product development area of the company. It was possible to treat the information obtained and establish discussions and conclusions around the main idea. The results of the research demonstrate that the user's participation in the development stages of a new product can impact on the reduction of the time used in the project execution if its planned correctly and applied since the initial stages of product design.
Managers' perspective on user participation in the project and reduction of process time
Keywords: Desenvolvimento de novos produtos; Envolvimento do usuário; Tempo de projeto; New product development; Design; User involvement; Time-to-market; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO